A study of the nature and determinants of customer experience in an increasingly commoditizing luxury retail sector - Siddiqui, Imaan Fatima (2016)
The purpose of this dissertation is to identify and assess the key determinants and antecedents of customer experience from the perspective of consumers, particularly in a luxury retail context. This dissertation provides an overview of the existing academic and practitioner literature on customer experience and expands on it by examining the creation and perception of customer experience within a luxury structure in an attempt to address this gap. The primary aim of this research is, therefore, to understand and highlight the elements of customer experience that most effectively enhance consumer-perceived experience and motivate consumers to distinguish between luxury retailers and create preference for one luxury retailer over another.